Polynitroso compounds, their preparation and electrochemical use

By preparing polynitroso compounds as cathode materials for lithium-ion batteries, the performance limitations of inorganic cathode materials and the solubility problems of organic radical materials are solved, and high specific capacity and stable energy storage performance are achieved.

CN118108603BActive Publication Date: 2025-08-01CITY UNIVERSITY OF HONG KONG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310150261.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-11-29
Filing Date
2023-02-22
Publication Date
2025-08-01
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

The performance of lithium-ion batteries of existing inorganic cathode materials is limited by specific capacity and energy density, while the application of organic radical materials in the field of electrode materials is limited by the problems of low conductivity and high solubility.

Method used

A polynitroso compound is developed, containing a single-cycle or polycyclic core on which two or more terminal nitroso groups are attached, prepared by nitroscopy reactions to increase electrical conductivity and reduce the solubility of free radical materials in the electrolyte.

Benefits of technology

It achieves high specific capacity and stable energy storage performance. Multi-nitroso compounds, as electrode materials, exhibit long-term free radical characteristics and excellent cycling stability in rechargeable lithium-ion batteries, are suitable for energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118108603B_ABST
    Figure CN118108603B_ABST
Patent Text Reader

Abstract

A polynitroso compound, the polynitroso compound comprising a monocyclic core or a polycyclic core to which two or more terminal nitroso groups are attached, such as formula (A) to formula (D), especially formula (VII). A method for preparing the polynitroso compound of the present invention. An energy storage device, the energy storage device having a cathode comprising the polynitroso compound of the present invention. There is also provided an electrode material for an energy storage device, the electrode material comprising a polynitroso compound having a monocyclic core containing at least one terminal nitroso group, such as formula (A) to formula (D), especially formula (VII).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to novel polynitroso compounds, particularly but not limited to polynitrosoaromatic compounds. The present invention also relates to the preparation of polynitroso compounds and their use as electrode materials, particularly but not limited to cathode materials for energy storage devices, particularly but not limited to rechargeable lithium-ion batteries. Background Art

[0002] Lithium-ion batteries (LIBs) have become one of the most important devices in the field of energy storage. However, their performance is limited by the limited specific capacity of inorganic cathode materials (theoretical specific capacity: <300 mAh g -1 ) and the strict limitations of low energy density.

[0003] Compared with inorganic cathode materials, organic cathode materials are believed to have potential advantages such as high theoretical specific capacity, diverse structures, environmental friendliness, and sustainable production. Among them, organic free radicals such as nitroxide radicals have been widely made into organic cathode materials and used in energy storage and battery research. Although these materials are believed to have advantages such as strong charge transfer ability, fast charge and discharge speed, long cycle life, good reversibility, and high redox potential, their inherent structural characteristics, low conductivity, and high solubility mean that they can only provide limited rate performance and rapid capacity decay, which seriously hinders their practical application in the field of electrode materials.

[0004] Studies have shown that by tethering free radical elements to conjugated or non-conjugated polymer backbones, the conductivity can be improved and the solubility of free radical element materials in the electrolyte can be reduced. However, the introduction of polymers not only complicates the synthesis of the free radical electrode materials and reduces the processability of the materials, but also often makes it difficult to explain the simple redox energy storage mechanism. In addition, the redundant polymer backbone will inevitably lead to a theoretical capacity of only about 110-130 mAh g -1 ) is greatly reduced, which seriously hinders its further application in the field of energy storage.

[0005] Therefore, there is an urgent need to develop new free radical materials that can serve as independent electrode materials and improve the comprehensive performance of energy storage devices to meet the growing demand for energy storage. Summary of the Invention

[0006] In a first aspect of the present invention, there is provided a polynitroso compound for use in an energy storage device, the polynitroso compound comprising a monocyclic core or a polycyclic core having two or more terminal nitroso groups attached thereto.

[0007] In one embodiment, the polynitroso compound comprises a structure having the formula:

[0008]

[0009]

[0010] wherein L1 to L4 are linking groups, and wherein: L1, if present, is a benzenoid; L2 and L3 are independently selected from an atom, an alkenyl group, a benzenoid or a macrocycle; and L4 is selected from a benzenoid or a macrocycle.

[0011] In one embodiment, wherein L1 comprises wherein R1 to R4 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, an aryl group, a halogen, and adjacent R1 to R4 may form a fused heterocycle or carbocycle; and

[0012] L5, if present, is an unsubstituted or substituted C2-C4 alkenyl group, a heterocycle or a carbocycle.

[0013] Preferably, R1 to R4 are the same and are selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group, a halogen, and adjacent R1 to R4 may form a fused 6-membered carbocycle; and

[0014] L5, if present, is a non-fused 6-membered carbocycle or a fused 6-membered carbocycle.

[0015] Preferably, the polynitroso compound comprises a structure having the following formula:

[0016]

[0017]

[0018] In one embodiment, L2 comprises a nitrogen atom or wherein R5 to R7 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group or a halogen; and

[0019] L6 to L8, if present, are the same and are carbocycles.

[0020] Preferably, R5 to R7 are the same and are selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group or a halogen; and

[0021] L6 to L8, if present, are 6-membered carbocycles.

[0022] Preferably, the polynitroso compound comprises a structure having the following formula:

[0023]

[0024]

[0025] In one embodiment, L3 contains carbon atoms, C2-C4 alkenyl, wherein R8 to R 15 are independently selected from a hydrogen atom, a halogen, or an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group;

[0026] R 16 to R 23 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, an aryl group, a halogen, and adjacent R 16 to R 23 can form a fused heterocyclic or carbocyclic ring; M is H2 or a metal atom;

[0027] R 24 to R 31 are independently selected from a hydrogen atom, a halogen, and an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group;

[0028] R 32 to R 41 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, a halogen, and adjacent R 32 to R 41 can form a fused heterocyclic or carbocyclic ring.

[0029] Preferably, R8 to R 13 are the same and are selected from a hydrogen atom and an unsubstituted straight-chain or branched C1-C6 alkyl group;

[0030] R 14 and R 15 are the same and are selected from a hydrogen atom and an unsubstituted straight-chain or branched C1-C6 alkyl group;

[0031] R 16 to R 23 are the same and are selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group, and adjacent R 16 to R 23 can form a fused 6-membered carbocyclic ring; M is H2 or a metal atom selected from iron, nickel, copper, zinc, or manganese;

[0032] R 24 to R 31 are the same and are selected from a hydrogen atom and an unsubstituted straight-chain or branched C1-C6 alkyl group; and

[0033] R 32 to R 41 are the same and are selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group, and adjacent R 32 to R 41A fused 6-membered carbon ring can be formed.

[0034] Preferably, the polynitroso compound comprises a structure having the following formula:

[0035]

[0036]

[0037]

[0038] In one embodiment, L4 comprises a 6-membered carbon ring. Preferably, the polynitroso compound comprises a structure having the following formula:

[0039]

[0040] In one embodiment, the polynitroso compound includes monomeric form, polymeric form, and combinations thereof.

[0041] In one embodiment, the polynitroso compound is a compound radical. Preferably, the compound radical remains active for at least 6 months.

[0042] In one embodiment, the energy storage device includes a rechargeable lithium-ion battery.

[0043] In a second aspect of the present invention, there is provided a method for preparing a polynitroso compound according to the first aspect of the present invention, the method comprising the following steps:

[0044] a) providing a precursor compound comprising two or more terminal trifluoroborate groups or silyl groups; and

[0045] b) nitrosating the precursor compound with a nitrosating agent.

[0046] In one embodiment, the terminal trifluoroborate group includes trifluoroborate salts. Preferably, the trifluoroborate salt is potassium trifluoroborate.

[0047] In one embodiment, the terminal silyl group is trimethylsilyl.

[0048] In one embodiment, the nitrosating agent includes nitronium salts. Preferably, the nitronium salts are selected from the group consisting of nitrosyl bromide, nitrosyl chloride, nitrosyl sulfuric acid, potassium nitrite, sodium nitrite, silver nitrite, nitronium tetrafluoroborate, and combinations thereof. [[ID=***]]

[0049] In one embodiment, the nitrosation is carried out under neutral or acidic conditions.

[0050] Preferably, the acidic condition is adjusted by hydrochloric acid, hydrobromic acid, sulfuric acid, or a combination thereof.

[0051] In one embodiment, the precursor compound is provided in the form of a reaction solvent mixture.

[0052] Preferably, the reaction solvent is selected from the group consisting of 1,2-dichlorobenzene, dichloromethane, 1,2-dichloroethane, tetrahydrofuran, n-hexane, heptane, ethyl acetate, toluene, acetonitrile, and combinations thereof.

[0053] In some embodiments, the reaction solvent is acetonitrile.

[0054] Preferably, step b) includes preparing a reaction mixture of the precursor compound and the nitrosating agent at an A:B molar ratio, where A is from about 2 to about 4, and B is from about 3 to about 10.

[0055] In a third aspect, the present invention provides an energy storage device having a cathode comprising a polynitroso compound according to the first aspect of the present invention.

[0056] In one embodiment, the energy storage device has a stable discharge capacity of from about 270 mA h g -1 to about 1 A g -1 at a current density of from about 50 mA g -1 to about 117 mA h g -1 within a voltage window of from about 1.3 V to about 4.3 V.

[0057] In one embodiment, the energy storage device has a specific capacity of about 300 mA h g -1 at a current density of about 100 mA g -1 after 100 charge / discharge cycles.

[0058] In one embodiment, the energy storage device has a capacity retention rate of about 85% after about 1000 charge / discharge cycles at a current density of about 1 A g -1 .

[0059] Preferably, the energy storage device is a rechargeable lithium-ion battery.

[0060] According to a fourth aspect of the present invention, there is provided an electrode material for an energy storage device, the electrode material comprising a polynitroso compound having a monocyclic core containing at least one terminal nitroso group.

[0061] Preferably, the polynitroso compound comprises a structure having the following formula:

[0062]

[0063]

[0064] Wherein L1 to L4 are linking groups, and wherein: L1, if present, is a benzenoid compound; L2 and L3 are independently selected from atoms, alkenyl groups, benzenoid compounds or macrocycles; and L4 is selected from benzenoid compounds or macrocycles.

[0065] In one embodiment, the polynitroso compound comprises a structure having the following formula:

[0066]

[0067]

[0068] In one embodiment, the polynitroso compound comprises a structure having the following formula:

[0069]

[0070] In one embodiment, the polynitroso compound comprises a structure having the following formula:

[0071]

[0072]

[0073] In one embodiment, the polynitroso compound comprises a structure having the following formula:

[0074]

[0075] Preferably, the electrode material is a cathode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 Shows the Fourier transform infrared (FT-IR) spectra of polynitroso compounds VII, VIII, XI and XV.

[0077] Figure 2 Are the FT-IR spectra of polynitroso compounds I, II, III, V and VI.

[0078] Figure 3 Are the electron paramagnetic resonance (EPR) spectra of polynitroso compounds VII, VIII and XI.

[0079] Figure 4 Is the synthesis scheme of polynitroso compound I.

[0080] Figure 5 Is the synthesis scheme of polynitroso compound II.

[0081] Figure 6 is the synthesis scheme of polynitroso compound III.

[0082] Figure 7 is the synthesis scheme of polynitroso compound V.

[0083] Figure 8 is the synthesis scheme of polynitroso compound VI.

[0084] Figure 9 is the synthesis scheme of polynitroso compound VII.

[0085] Figure 10 is the synthesis scheme of polynitroso compound VIII (i.e., the polynitroso compound of formula (VII) of the present invention, TPA-3NO).

[0086] Figure 11 is the synthesis scheme of polynitroso compound X.

[0087] Figure 12 is the synthesis scheme of polynitroso compound XI.

[0088] Figure 13A is the 1 H-nuclear magnetic resonance (NMR) spectrum of TPA-3Br prepared according to an embodiment of the present invention.

[0089] Figure 13B is the 13 C-NMR spectrum of TPA-3Br prepared according to an embodiment of the present invention.

[0090] Figure 14A is the 1 H-NMR spectrum of TPA-3TMS prepared according to an embodiment of the present invention.

[0091] Figure 14B is the 13 C-NMR spectrum of TPA-3TMS prepared according to an embodiment of the present invention.

[0092] Figure 15A is the 1 H-NMR spectrum of TPA-3NO prepared according to an embodiment of the present invention. The inset is the enlarged spectrum from about 6.6 to about 8.6 ppm.

[0093] Figure 15B is the 13 C-NMR spectrum of TPA-3NO prepared according to an embodiment of the present invention.

[0094] Figure 16 is the synthesis scheme of 1-bromo-4-nitroso benzene.

[0095] Figure 17A is the 1 1H-NMR spectrum of (4-bromophenyl)trimethylsilane.

[0096] Figure 17B is the 13 13C-NMR spectrum of (4-bromophenyl)trimethylsilane.

[0097] Figure 18A is the 19 19F-NMR spectrum of TPA-3NO prepared according to an embodiment of the present invention with or without washing with deionized water. The inset is an enlarged portion of the highlighted part of the spectrum. The absence of 19 19F signals indicates the absence of inorganic residual impurities in the resulting TPA-3NO.

[0098] Figure 18B is the 11 11B-NMR spectrum of TPA-3NO prepared according to an embodiment of the present invention with or without washing with deionized water. The inset is an enlarged portion of the highlighted part of the spectrum. The absence of 11 11B signals indicates the absence of inorganic residual impurities in the resulting TPA-3NO.

[0099] Figure 19 is the 1 1H-NMR spectrum of TPA-3NO in CDCl3 before and after 3 weeks.

[0100] Figure 20 is a plot of weight versus time at 200 °C, which shows the results of thermogravimetric analysis (TGA) of TPA-3NO.

[0101] Figure 21A is the UV / Vis absorption spectrum of TPA-3NO in chloroform (10 -5 M).

[0102] Figure 21B is the UV / Vis absorption spectrum of TPA-3NO in thin film.

[0103] Figure 21C is the FT-IR spectrum of TPA-3NO.

[0104] Figure 21D is the solid-state structure of TPA-3NO resolved by SCXRD analysis (CCDC number: 2207880).

[0105] Figure 21E is the EPR spectrum of TPA-3NO and 1-bromo-4-nitrobenzene powder samples.

[0106] Figure 21F It is the EPR spectrum of TPA-3NO powder stored in the atmospheric environment for 6 months.

[0107] Figure 22 It is a fluorescence comparison photograph showing the fluorescence between TPA-3NO excited by 365 nm light and commercially available tris(4-nitrophenyl)amine.

[0108] Figure 23 It is a cyclic voltammogram showing the cyclic voltammetry (CV) curve of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at 0.2 mV s -1 -1.

[0109] Figure 24A It is a graph of capacity versus cycle number, which shows the rate performance of TPA-3NO in 0.3 M LiTFSI-PY13TFSI.

[0110] Figure 24B It is a graph showing the cycling performance of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at 100 mA g -1 -1.

[0111] Figure 24C It is a graph illustrating the comparison of the theoretical capacity and the actual capacity of the organic radical cathode material in LIB.

[0112] Figure 25A It is a graph of voltage versus capacity, which shows the charge / discharge curves of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at different current densities.

[0113] Figure 25B It is a graph of voltage versus capacity, which shows the charge / discharge curves of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at 100 mA g -1 -1 with respect to different cycle numbers.

[0114] Figure 26A It is a cyclic voltammogram showing the CV curves of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at different scan rates.

[0115] Figure 26B It is a graph showing the relationship between log i and log v.

[0116] Figure 26C It is a bar graph showing the capacitive and diffusion-controlled capacity contributions of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at different scan rates.

[0117] Figure 26DIt is a graph showing the cycling performance of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at 1 A g -1 below.

[0118] Figure 26E It is a graph showing the cycling performance of TPA-3NO in 0.3 M LiTFSI-PY13TFSI at 2 A g -1 below.

[0119] Figure 27 It is the electrochemical impedance spectroscopy graph of TPA-3NO in 0.3 M LiTFSI-PY13TFSI.

[0120] Figure 28 It is a schematic diagram showing the mechanism of the proposed charging and discharging processes of TPA-3NO.

[0121] Figure 29A It is the ex-situ FT-IR spectrum of TPA-3NO during the charging and discharging processes.

[0122] Figure 29B It is corresponding to Figure 29A the graph of capacity versus voltage.

[0123] Figure 30A It is the ex-situ XPS spectrum of C1s of TPA-3NO in the recharging / discharging state.

[0124] Figure 30B It is the ex-situ XPS spectrum of N1s of TPA-3NO in the recharging / discharging state.

[0125] Figure 30C It is the ex-situ XPS spectrum of O1s of TPA-3NO in the recharging / discharging state.

[0126] Figure 30D It is the ex-situ XPS spectrum of F1s of TPA-3NO in the recharging / discharging state.

[0127] Figure 30E It is the ex-situ XPS spectrum of S 2p of TPA-3NO in the recharging / discharging state. Detailed implementation manners

[0128] Unless otherwise specifically provided, all tests herein are conducted under standard conditions including room temperature and test temperature of 25 °C, sea level (1 atm.) pressure, and pH 7, and all measurements are made in metric units. In addition, unless otherwise expressly indicated, all percentages, ratios, etc. herein are by weight. It should be understood that unless otherwise specifically stated, the material compounds, chemicals, etc. described herein are typically commercially available and / or industrial standard articles obtainable from multiple suppliers around the world.

[0129] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0130] Unless the context clearly indicates otherwise, as used herein, the forms "a / an" and "the" are intended to include both singular and plural forms.

[0131] As used in this application, the term "or" is intended to mean an inclusive "or" rather than an exclusive "or". That is, unless otherwise stated or clear from the context, "X employs A or B" is intended to mean any natural inclusive arrangement. That is, if X employs A; X employs B; or X employs both A and B, then "X employs A or B" holds in any of the foregoing cases.

[0132] Theoretically, the nitroso (NO) group can be oxidized to a nitro group through a 2e - transfer process, or directly reduced to an amine through a 4e - transfer process. The multiple electron conversion processes endow it with potential applications in LIBs. For example, based on the 4e - reduction process, the theoretical specific capacity of one NO group can be as high as about 3573 mAh g -1 . Without intending to be bound by theory, the inventors have designed, through their own research, tests, and experiments, a class of polynitroso compounds, particularly polynitrosoarenes, which are characterized by being chemically stable in an atmospheric environment and having (open-shell) radical characteristics. In particular, the inventors unexpectedly found that the radical characteristics of the polynitroso compounds can be maintained for a quite long time. In an exemplary embodiment, the radical characteristics of the polynitroso compounds can remain active for at least 6 months. Therefore, the polynitroso compounds described herein may be used as organic radical cathode materials for rechargeable batteries such as LIBs, organic radical batteries (ORBs), etc.

[0133] According to the present invention, there is provided a polynitroso compound for an energy storage device, the polynitroso compound comprising a monocyclic core or a polycyclic core to which two or more terminal nitroso groups are attached. As used herein, the term "polynitroso compound" generally refers to an organic compound having at least one or more nitroso (NO) groups, such as two or more, two to three, two to four, two to five, two to six, two to seven, two to eight nitroso groups, etc. In particular, the polynitroso compound may have two to six nitroso groups. In an embodiment of the present invention, the polynitroso compound may have two, three, four or six nitroso groups. The nitroso groups are particularly terminal nitroso groups. The term "terminal" should be understood in the art to describe a chemical functional group, such as the nitroso group as described herein, which is located / tethered / bonded to the end of a carbon chain or the outer periphery of a cyclic ring. In particular, these terminal nitroso groups are attached (preferably by a covalent bond) to a monocyclic or polycyclic core.

[0134] A monocyclic core generally refers to a group of atoms that are connected to form a monocyclic structure. The atoms within the monocyclic core can all be carbon (i.e., a carbocyclic core), or both carbon atoms and non-carbon atoms (i.e., a heterocyclic core). The ring size of the monocyclic core can vary from, for example, three to eight, three to seven, three to six, three to five or three to four. Depending on the ring size, the monocyclic core can also have different numbers of saturated and unsaturated bonds (i.e., double bonds and triple bonds). In particular, the monocyclic core can include an unsubstituted or substituted C3-C10 carbocyclic ring, an unsubstituted or substituted C2-C5 heterocyclic ring, an unsubstituted or substituted macrocycle, a monoaromatic hydrocarbon, etc.

[0135] The carbocyclic ring can include an unsubstituted C3-C10 cycloalkane, cycloalkene, cycloalkyne or their derivatives substituted by, such as methyl, ethyl, isopropyl, hydroxy, halogen, phenyl, etc. Examples of unsubstituted C3-C10 cycloalkanes, cycloalkenes and cycloalkynes can include cyclopropane, cyclobutane, cyclopentane, cyclohexane, cyclopentene, cyclopentadiene, cyclohexene, cyclohexadiene, cyclononyne, cyclodecyne, etc.

[0136] The unsubstituted C2-C5 heterocyclic ring can include a three-membered ring having one heteroatom, a four-membered ring having one or two heteroatoms, a five-membered ring having one to three heteroatoms and a six-membered ring having one to three heteroatoms. The heteroatoms can be selected from nitrogen, oxygen, sulfur and their combinations. Examples can include aziridine, 2H-aziridine, ethylene oxide, thioethylene oxide, azetidine, oxetane, thietane, pyrrolidine, pyrroline, furan, pyrrole, oxazole, isothiazole, piperidine, pyridine, piperazine, pyrazine, triazine, dithiane, etc. In an embodiment where the C2-C5 heterocyclic ring is substituted, the substituents can be methyl, ethyl, isopropyl, hydroxy, halogen, phenyl, etc.

[0137] A macrocycle can refer to an organic compound containing a ring with twelve or more atoms. Specifically, a macrocycle can refer to a heterocyclic macrocycle, such as a crown ether, calixarene, porphyrin, cyclodextrin, etc., which may or may not be substituted by one or more of methyl, ethyl, isopropyl, hydroxyl, halogen, phenyl, carboxyl, etc.

[0138] Monocyclic aromatic hydrocarbons specifically refer to benzene or its derivatives, such as those substituted by one or more of methyl, ethyl, isopropyl, hydroxyl, halogen, amine, etc. Examples of benzene derivatives can include toluene, ethylbenzene, p-xylene, m-xylene, mesitylene, durene, 2-phenylhexane, phenol, aniline, etc.

[0139] As used herein, a polycyclic core generally can refer to a group of monocyclic structures connected / bonded together by fusion (i.e., edge-to-edge), tethering, and combinations thereof. In particular, a polycyclic core can include polycyclic cycloalkanes, polycyclic aromatic hydrocarbons, heterocyclic aromatic compounds having multiple rings, etc. Examples of polycyclic cores can include tricyclohexylamine, triphenylamine, tetracyclohexylmethane, tetraphenylmethane, biphenyl, triphenylbenzene, naphthalene, fluorene, 6,12-dihydroindeno[1,2-b]fluorene, anthracene, phenanthrene, chrysene, tetracene, pyrene, triphenyl, tetraphenylethylene, etc., or any of the above substituted by one or more of methyl, ethyl, isopropyl, hydroxyl, halogen, amine, phenyl, etc.

[0140] In certain embodiments, a polynitroso compound can comprise a structure having the following formula:

[0141]

[0142]

[0143] wherein L1 to L4 are linking groups, and wherein:

[0144] L1, if present, is a benzene ring-type compound; L2 and L3 are independently selected from an atom, an alkenyl group, a benzene ring-type compound, or a macrocycle; and L4 is selected from a benzene ring-type compound or a macrocycle.

[0145] The term "benzene ring-type compound" generally denotes an organic compound having at least one benzene ring. For example, it can be benzene or its derivatives as described herein, or polycyclic cycloalkanes, polycyclic aromatic hydrocarbons, heterocyclic aromatic compounds having multiple rings as described herein. The atom is preferably an atom whose valence electrons are completely occupied after connecting to the nitrosoarene moiety. For example, referring to formulas (B) and (C), preferably L2 and L3 are a nitrogen atom and a carbon atom, respectively. The alkenyl group can be an unsubstituted or substituted C2-C4 alkenyl group, such as vinyl, propenyl, butenyl with or without being substituted by methyl, ethyl, isopropyl, hydroxyl, halogen, amine, phenyl, etc. The macrocycle can be the macrocycle as described herein.

[0146] In one embodiment, L1 may comprise

[0147] wherein R1 to R4 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, an aryl group, a halogen, and adjacent R1 to R4 may form a fused heterocyclic or carbocyclic ring; and

[0148] L5, if present, is an unsubstituted or substituted C2-C4 alkenyl group, a heterocyclic ring or a carbocyclic ring. [[ID=IO]]

[0149] In embodiments where R1 to R4 are an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, the alkyl group may refer to a straight-chain or branched hydrocarbon chain having 1 to 6 carbon atoms with or without substitution by one or more of halogens such as fluoride, chloride, bromide and iodide, hydroxy group, phenyl group, amino group, etc. Examples of the straight-chain or branched C1-C6 alkyl group may include methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, isobutyl, sec-butyl, tert-pentyl, 3-pentyl, etc.

[0150] In embodiments where R1 to R4 are an aryl group, the aryl group may refer to an aromatic hydrocarbon, particularly an aromatic hydrocarbon derived from benzene, such as phenyl, naphthyl, tolyl, xylyl, hydroxyphenyl, halophenyl (i.e., phenyl substituted by halogens such as fluoride, chloride, bromide or iodide), etc.

[0151] [ In embodiments where R1 to R4 are a halogen, it may be and is selected from halogens such as fluoride, chloride, bromide and iodide. The halogen on R1 to R4, if present, is preferably the same.

[0152] In one embodiment, adjacent R1 to R4 may form a fused heterocyclic or carbocyclic ring. That is, for example, R1 and R2 and / or R3 and R4 may form a fused heterocyclic or carbocyclic ring. In particular, the fused heterocyclic ring may be a C2-C5 heterocyclic ring as described herein, and the fused carbocyclic ring may be an unsubstituted C3-C10 cycloalkane, cycloalkene, cycloalkyne or derivatives thereof as described herein, or benzene or derivatives thereof as described herein.

[0153] Preferably, R1 to R4 are the same and are selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group (such as an unsubstituted straight-chain or branched C1-C3 alkyl group such as methyl, ethyl, propyl, isopropyl), a halogen as described herein, and adjacent R1 to R4 may form a fused 6-membered carbocyclic ring such as benzene or cyclohexane; and

[0154] L5, if present, is a non-fused 6-membered carbocyclic ring such as benzene, cyclohexane, cyclohexene, cyclohexa-1,3-diene, cyclohexa-1,4-diene; or a fused 6-membered carbocyclic ring such as naphthalene, anthracene, phenanthrene, fluoranthene, tetracene, pyrene, etc.

[0155] As a specific embodiment, the polynitroso compound having the structure of formula (A) may comprise a structure having the following formula:

[0156]

[0157] In one embodiment, L2 may comprise a nitrogen atom or

[0158] wherein R5 to R7 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, or a halogen; and

[0159] L6 to L8, if present, are the same and are a carbocyclic ring.

[0160] The unsubstituted or substituted straight-chain or branched C1-C6 alkyl group may refer to a straight-chain or branched hydrocarbon chain having 1 to 6 carbon atoms with or without substitution by one or more of a halogen such as fluoride, chloride, bromide, and iodide, a hydroxyl group, a phenyl group, an amino group, etc. Examples of the straight-chain or branched C1-C6 alkyl group may include those described above. The halogen on R5 to R7 may be fluoride, chloride, bromide, or iodide, and preferably, if present, they are the same. The carbocyclic ring may be an unsubstituted or substituted C3-C10 carbocyclic ring or a monoaromatic hydrocarbon as described herein.

[0161] In particular, R5 to R7 are the same and are selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group (such as an unsubstituted straight-chain or branched C1-C3 alkyl group such as methyl, ethyl, propyl, isopropyl), or a halogen as described herein; and

[0162] L6 to L8, if present, are a 6-membered carbocyclic ring such as benzene, cyclohexane, cyclohexene, cyclohex-1,3-diene, cyclohex-1,4-diene.

[0163] As a specific embodiment, the polynitroso compound having the structure of formula (B) may comprise a structure having the following formula:

[0164]

[0165]

[0166] In one embodiment, L3 may comprise a carbon atom, a C2-C4 alkenyl group,

[0167] wherein R8 to R 15 are independently selected from a hydrogen atom, a halogen, or an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group;

[0168] R16 to R 23 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, an aryl group, and a halogen, and adjacent Rs 16 to R 23 may form a fused heterocyclic or carbocyclic ring; M is H2 or a metal atom;

[0169] R 24 to R 31 are independently selected from a hydrogen atom, a halogen, and an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group;

[0170] R 32 to R 41 are independently selected from a hydrogen atom, an unsubstituted or substituted straight-chain or branched C1-C6 alkyl group, and a halogen, and adjacent Rs 32 to R 41 may form a fused heterocyclic or carbocyclic ring.

[0171] The C2-C4 alkenyl group may be an unsubstituted or substituted alkenyl group having 2 to 4 carbon atoms, such as vinyl, propenyl, or butenyl with or without substitution by methyl, ethyl, isopropyl, hydroxy, halogen, amine, phenyl, etc.

[0172] The unsubstituted or substituted straight-chain or branched C1-C6 alkyl group on R8 to R 41 may refer to a straight-chain or branched hydrocarbon chain having 1 to 6 carbon atoms with or without substitution by one or more of a halogen such as fluoride, chloride, bromide, and iodide, hydroxy, phenyl, amino, etc. Examples of the straight-chain or branched C1-C6 alkyl group may include those described above. The halogen on R8 to R 41 may be fluoride, chloride, bromide, or iodide, and if present, it is preferred that the halogen in each of the following groups is the same: R8 to R 13 , R 14 and R 15 , R 16 to R 23 and R 32 to R 41 .

[0173] The aryl group on R 16 to R 23 , if present, may refer to an aromatic hydrocarbon, particularly an aromatic hydrocarbon derived from benzene, such as phenyl, naphthyl, tolyl, xylyl, hydroxyphenyl, halophenyl, etc.

[0174] Adjacent Rs 16 to R 23 and R 32 to R 41A fused heterocycle or carbocycle can be formed. That is, for example, one or more of the following pairs can form a fused heterocycle or carbocycle: R 16 and R 17 、R 18 and R 19 、R 20 and R 21 、R 22 and R 23 、R 32 and R 33 、R 33 and R 34 、R 34 and R 35 、R 38 and R 39 、R 39 and R 40 and R 40 and R 41 . The fused heterocycle can be a C2-C5 heterocycle as described herein, and the fused carbocycle can be an unsubstituted C3-C10 cycloalkane, cycloalkene, cycloalkyne or their derivatives as described herein, or benzene or its derivatives as described herein. M in L3 can be H2 or a metal atom. In the embodiment where M is H2, it means that two hydrogen atoms are provided to bond to two nitrogen atoms in the adjacent nitrogen-containing five-membered ring to form a -NH bond, that is, to form pyrrole. The metal atom can be selected from iron, cobalt, nickel, copper, zinc, titanium, vanadium, chromium, manganese, molybdenum, zirconium, cadmium, antimony, niobium, palladium or platinum.

[0175] In particular, R8 to R 13 are the same and are selected from a hydrogen atom and an unsubstituted straight-chain or branched C1-C6 alkyl group, such as an unsubstituted straight-chain or branched C1-C3 alkyl group, such as methyl, ethyl, propyl, isopropyl;

[0176] R 14 and R 15 are the same and are selected from a hydrogen atom and an unsubstituted straight-chain or branched C1-C6 alkyl group; such as an unsubstituted straight-chain or branched C1-C3 alkyl group, such as methyl, ethyl, propyl, isopropyl;

[0177] R 16 to R 23 are the same and are selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group, such as an unsubstituted straight-chain or branched C1-C3 alkyl group, such as methyl, ethyl, propyl, isopropyl, and adjacent R 16 to R 23 can form a fused 6-membered carbocycle, such as benzene or cyclohexane; M is H2 or a metal atom selected from iron, nickel, copper, zinc or manganese;

[0178] R 24 to R 31identical and selected from a hydrogen atom and an unsubstituted straight-chain or branched C1-C6 alkyl group, such as an unsubstituted straight-chain or branched C1-C3 alkyl group, such as methyl, ethyl, propyl, isopropyl; and

[0179] R 32 to R 41 are identical and selected from a hydrogen atom, an unsubstituted straight-chain or branched C1-C6 alkyl group, such as an unsubstituted straight-chain or branched C1-C3 alkyl group, such as methyl, ethyl, propyl, isopropyl, and adjacent R 32 to R 41 may form a fused 6-membered carbon ring, such as benzene and cyclohexane.

[0180] As a specific embodiment, the polynitroso compound having the structure of formula (C) may comprise a structure having the following formula:

[0181]

[0182]

[0183] In one embodiment, L4 may comprise a 6-membered carbon ring, such as benzene, cyclohexane, cyclohexene, cyclohex-1,3-diene, cyclohex-1,4-diene. As a specific embodiment, the polynitroso compound having the structure of formula (D) may comprise a structure having the following formula:

[0184]

[0185] The polynitroso compounds of the present invention may include monomeric forms, polymeric forms, and combinations thereof. The term "polymeric" generally means that two or more polynitroso compound molecules may be linked by chemical bonds such as covalent bonds or intermolecular bonds. For example, the polynitroso compounds may be arranged in a dimeric form (i.e., two polynitroso compound molecules are linked by an intermolecular bond such as a cis or trans azodioxo bond), a trimeric form, a tetrameric form, a pentameric form, a hexameric form, etc.

[0186] The monomeric or polymeric form of the polynitroso compound may be characterized by FT-IR spectroscopy. For example, in an embodiment where the polynitroso compound is in monomeric form, it typically has characteristic absorption peaks at about 1485 cm -1 and 1101 cm -1 , which correspond to the stretching vibrations of N=O and C-N=O, respectively ( Figure 1 ). In another embodiment where the polynitroso compound is in polymeric form, it typically has a characteristic absorption peak at about 1255 cm -1 , corresponding to the stretching vibration of the trans-azodioxo bond ( Figure 2 ).

[0187] As described herein, it is believed that the polynitroso compounds of the present invention have free radical properties. In other words, the polynitroso compounds of the present invention are compound radicals. The term "compound radical" or "complex radical" generally describes a chemical species, particularly a compound molecule containing at least one unpaired electron. The free radical nature / characteristics of the polynitroso compounds can be characterized by electron paramagnetic resonance (EPR) spectroscopy. Referring to Figure 3 , for example, when the polynitroso compound has free radical properties (or has free radical activity), a sharp absorption curve will be observed in the EPR spectrum, and its corresponding g value, such as a g value of about 2.005, can be calculated. Otherwise, an absorption curve with such a peak will not be observed ( Figure 3 , 4-bromonitrosobenzene).

[0188] The free radical activity of the polynitroso compounds of the present invention can last for at least 6 months. That is to say, the polynitroso compound can maintain its activity as a compound radical for at least 6 months (i.e., the characteristics of the polynitroso compound as a compound radical can be maintained for at least 6 months). In an exemplary embodiment, the polynitroso compound (as a compound radical) can maintain its activity for about 6 months. Such a long-lasting free radical activity will make the polynitroso compounds of the present invention particularly suitable for applications in energy storage devices such as rechargeable batteries, such as rechargeable lithium-ion batteries, rechargeable organic radical batteries, etc.

[0189] The following describes a method for preparing a polynitroso compound, that is, a method for preparing a polynitroso compound having a structure of the following formula:

[0190]

[0191]

[0192] wherein L1 to L4 are as defined herein.

[0193] The method includes the following steps:

[0194] a) Providing a precursor compound containing two or more terminal trifluoroborate groups or silyl groups; and

[0195] b) Nitrosating the precursor compound with a nitrosating agent.

[0196] In one embodiment, the precursor compound can be a compound having a structure similar to that of formula (A) to formula (D), wherein the nitroso group is replaced by a terminal trifluoroborate group or a silyl group. The terminal trifluoroborate group can include trifluoroborates such as potassium trifluoroborate, and the terminal silyl group can be trimethylsilyl (TMS).

[0197] In certain embodiments, the precursor compound may comprise a structure having the following formula:

[0198]

[0199]

[0200]

[0201] wherein L1 to L4 are as defined herein.

[0202] In one embodiment, step a) may optionally include the step of preparing a precursor compound having a structure of formula (A1), formula (B1), formula (C1), or formula (D1) from their corresponding bromo-precursor compounds. In particular, the bromo-precursor may be a precursor in which the TMS group is replaced by a bromide. As an exemplary embodiment, when the precursor compound is a compound having a structure of formula (B1), the corresponding bromo-precursor compound may have a structure of formula (B3):

[0203]

[0204] wherein L2 is as defined herein.

[0205] In particular, the conversion of the bromo-precursor compound to the precursor compound having a structure of formula (A1), formula (B1), formula (C1), or formula (D1) can be carried out in the presence of an organolithium agent such as methyllithium, n-butyllithium, sec-butyllithium, isopropyllithium, tert-butyllithium, phenyllithium, etc. As a specific embodiment, the organolithium agent can be n-butyllithium (n-BuLi).

[0206] In another embodiment, step a) may optionally include the step of preparing a precursor compound having a structure of formula (A2), formula (B2), formula (C2), or formula (D2) from their corresponding boric acid-precursor compounds. As an exemplary embodiment, when the precursor compound is a compound having a structure of formula (B2), the corresponding boric acid-precursor compound may have a structure of formula (B4):

[0207]

[0208] wherein L2 is as defined herein.

[0209] In particular, the conversion of the boric acid-precursor compound to the precursor compound having a structure of formula (A2), formula (B2), formula (C2), or formula (D2) can be carried out in the presence of a fluorinating agent such as n-Bu4NHF2.

[0210] In alternative embodiments, boric acid-precursor compounds such as compounds having formula (B4) can react with organic halides such as organic bromides, particularly organic bromides substituted with (terminal) TMS groups, such as the organic bromide intermediate having the structure of formula (a):

[0211]

[0212] to form a precursor compound having the structure of formula (B1)':

[0213]

[0214] wherein L2 is as defined herein.

[0215] In particular, the reaction between the organic bromide intermediate and the boric acid-precursor compound can be carried out by a Suzuki (coupling) reaction. It should be understood in the art that such a reaction is a cross-coupling reaction, wherein the coupling partners, the boric acid precursor compound (such as the boric acid precursor compound having the structure of formula (B4) in one embodiment) and the organic halide (such as the organic bromide intermediate having the structure of formula (a) in one embodiment) will form a single C-C bond in the presence of a palladium(0) catalyst such as PdCl2(PPh3)2, Pd(PPh3)4, Pd(OAc)2(PPh3)2, etc.

[0216] Step b) particularly includes the following steps:

[0217] i) preparing a reaction mixture of the precursor compound and the nitrosating agent in a reaction solvent;

[0218] ii) stirring the reaction mixture for at least about 30 minutes at at least about 20 °C; and

[0219] iii) separating the polynitroso compound having the structure of formula (A), formula (B), formula (C) or formula (D) and optionally purifying the polynitroso compound.

[0220] In one embodiment, the precursor compound can be provided in the form of a solvent mixture. That is, the precursor compound can be in the form of a mixture with at least a portion of the reaction solvent.

[0221] In particular, the reaction solvent is selected from the group consisting of: 1,2-dichlorobenzene, dichloromethane, 1,2-dichloroethane, tetrahydrofuran, n-hexane, heptane, ethyl acetate, toluene, acetonitrile, and combinations thereof. As a specific embodiment, the reaction solvent is acetonitrile.

[0222] The nitrosating agent can be a nitronium salt. In particular, the nitronium salt can optionally be selected from the group consisting of nitrosyl bromide (NOBr), nitrosyl chloride (NOCl), nitrosyl sulfuric acid (NOHSO4), potassium nitrite (KNO2), sodium nitrite (NaNO2), silver nitrite (AgNO2), nitronium tetrafluoroborate (BF4NO), and combinations thereof. As a specific embodiment, the nitrosating agent is BF4NO.

[0223] The nitrosation can be carried out under neutral or acidic conditions. In embodiments where the nitrosation is carried out under acidic conditions, the acidic conditions can be adjusted by hydrochloric acid, hydrobromic acid, sulfuric acid, or combinations thereof.

[0224] The reaction mixture of the precursor compound and the nitrosating agent in step bi) can have a predetermined molar ratio. In particular, the precursor compound and the nitrosating agent can be mixed in a molar ratio of A:B. Preferably, A is about 2 to about 4, about 1.9 to about 4, about 2.1 to about 4, about 2 to about 3.9, about 2 to about 4.1, or 1.9 to about 4.1. Also preferably, B is about 3 to about 10, about 3 to about 10.2, about 3 to about 10.1, about 2.9 to about 10, about 2.9 to about 10.1, about 2.9 to about 10.2, about 3.3 to about 10.2, or about 3.4 to about 10.2.

[0225] In a preferred embodiment, the precursor compound and the nitrosating agent in step bi) are mixed in a predetermined molar ratio to obtain a polynitroso compound having a specific structure. In an exemplary embodiment where A:B is 2:3.4, a polynitroso compound having the structure of formula (A) can be preferably obtained. In another exemplary embodiment where A:B is 3:5.1, a polynitroso compound having the structure of formula (B) can be preferably obtained. In another exemplary embodiment where A:B is 4:6.8, a polynitroso compound having the structure of formula (C) can be preferably obtained. In yet another exemplary embodiment where A:B is 4:10.2, a polynitroso compound having the structure of formula (D) can be preferably obtained.

[0226] "Isolating" the polynitroso compound means at least partially separating the compound from other components such as by-products, reactants, and reaction solvents present in the reaction mixture after step bii).

[0227] Step (iii) can particularly include filtering the reaction mixture to obtain a filtrate, centrifuging the reaction mixture so that the polynitroso compound forms a precipitate in water such as cold water or a salt solution such as sodium chloride, potassium chloride, sodium carbonate, sodium bicarbonate, sodium acetate, or ammonium chloride solution, adding a precipitation solvent to the filtrate to obtain a precipitate, and washing the precipitate with a washing solvent.

[0228] The purification step in step biii) can be performed by column chromatography such as silica gel column chromatography, alumina column chromatography, recrystallization, and the like.

[0229] The polynitroso compound obtained after step biii) can be optionally dried under vacuum at about room temperature to about 50°C, about 50°C-70°C, about 70°C-90°C, about 90°C-110°C for about 4 hours to 6 hours, about 6 hours to 8 hours, about 8 hours to 12 hours, about 8 hours to 14 hours, about 10 hours to 12 hours.

[0230] As a specific embodiment, the method can be used to prepare polynitroso compounds having the structures of Formula (I) to Formula (XIX) as described herein.

[0231] Another aspect of the present invention relates to an electrode material for an energy storage device, the electrode material comprising a polynitroso compound having a monocyclic core containing at least one terminal nitroso group.

[0232] In particular, the polynitroso compound may comprise a structure having the formula:

[0233]

[0234]

[0235] wherein L1 to L4 are as defined herein.

[0236] In embodiments where the polynitroso compound has the structure of formula (A), the polynitroso compound may comprise a structure having the formula:

[0237]

[0238]

[0239] In embodiments where the polynitroso compound has a structure of formula (B), the polynitroso compound may comprise a structure having the formula:

[0240]

[0241]

[0242] In embodiments where the polynitroso compound has a structure of formula (C), the polynitroso compound may comprise a structure having the formula:

[0243]

[0244]

[0245]

[0246] In an embodiment where the polynitro compound has the structure of formula (D), the polynitro compound may comprise a structure having the following formula:

[0247]

[0248] As a specific embodiment, the polynitro compound, particularly the polynitro compound having the structure of formula (VII), can be used as a cathode material for a lithium-ion battery. For example, the polynitro compound, particularly the polynitro compound having the structure of formula (VII), can be mixed with a conductive material such as conductive carbon (such as Ketjen Black) and a binder such as polyvinylidene fluoride (PDVF) in a predetermined weight ratio such as about 3:5:2 in the presence of a solvent such as 1-methyl-2-pyrrolidone (NMP) to form a slurry. Then, the slurry can be coated on a metal sheet such as an aluminum sheet using, for example, a coater. The formed assembly (i.e., the crude cathode) can then be dried in vacuo at about 60 °C, about 65 °C, about 70 °C, about 75 °C, about 80 °C, about 85 °C, about 90 °C, about 95 °C, about 100 °C, about 105 °C or about 110 °C for about 6 to 16 hours, about 6 to 9 hours, about 6 to 12 hours, about 9 to 12 hours, about 9 to 16 hours, preferably about 12 hours, to remove the solvent.

[0249] The cathode as described herein can be assembled onto an energy storage device for operation. Accordingly, the present invention further relates to an energy storage device having a cathode comprising a polynitro compound as described herein. The energy storage device is particularly a rechargeable battery having an electrolyte, an anode, and a cathode in electrical communication, the cathode comprising a polynitro compound as described herein. The selection of the anode and the electrolyte can depend on the type of battery. For example, when the battery is a lithium-ion battery, the anode can be lithium metal, its alloy, or any other material intercalated with lithium ions, such as a graphite material intercalated with lithium ions; and the electrolyte can be an electrolyte containing lithium ions. The electrolyte can be in the form of an aqueous solution, an organic solution, a solid, a gel (such as a hydrogel), etc. When the electrolyte is in the form of an aqueous solution or an organic solution, the battery preferably has a separator to prevent the battery from short-circuiting during operation. The shape of the battery can be various, such as coin-shaped, rod-shaped, rectangular, cylindrical, etc.

[0250] In one embodiment, the energy storage device can be a rechargeable lithium-ion battery. The battery can be implemented as a button battery, which includes a cathode containing a polynitro compound of the present invention such as a polynitro compound having the structure of formula (VII), an anode containing lithium such as lithium metal, and an electrolyte containing LiTFSI and PY13TFSI. The button battery can include a separator that separates the anode and the cathode within the battery.

[0251] As described herein, it is believed that the polynitroso compounds of the present invention are suitable for energy storage devices. In particular, it is believed that the redox-active sites provided by the nitrogen or oxygen atoms of the nitroso group and the monocyclic or polycyclic core, especially those redox-active sites with aromaticity, can promote ion diffusion in the device (e.g., ion insertion and extraction), and thus provide excellent stability of the electrode in the electrolyte and maximize the capacity and reversibility of the device.

[0252] In one embodiment, the device can have a stable discharge capacity of about 270 mA h g -1 to about 1 A g -1 at a current density of from about 1.3 V to about 4.3 V in a voltage window. -1 to about 117 mA h g -1

[0253] In another embodiment, the device can have a specific capacity of about 300 mA h g -1 after 100 charge / discharge cycles at a current density of about 100 mA g -1

[0254] In another embodiment, the device can have a capacity retention rate of about 85% after about 1000 charge / discharge cycles at a current density of about 1 A g -1

[0255] Embodiment

[0256] Materials and Reagents Used

[0257] All reagents and solvents were obtained from commercial suppliers and used without further purification. Triphenylamine (TPA) and N-bromosuccinimide (NBS) were purchased from TCI; Nitrosyl tetrafluoroborate (BF4NO) was purchased from Thermo Scientific (Alfa Aesar); n-Butyllithium (2.5 M in hexane), 1-Bromo-4-(trimethylsilyl)benzene and Trimethylchlorosilane were purchased from Macklin. Tetrahydrofuran was dried by treatment with sodium and distilled.

[0258] The cathode was prepared by coating a slurry of the active material (tris(4-nitrosophenyl)amine, TPA-3NO (Formula (VII) of the present invention)) as the conductive carbon Vulcan XC-72 and polyvinylidene fluoride (PVDF) (Sigma-Aldrich) as the binder on aluminum foil in a weight ratio of 3:5:2. 1-Methyl-2-pyrrolidone (NMP) was used as the solvent. Then, the slurry was cast on an aluminum foil current collector and dried at 60 °C under vacuum for 12 h. CR2032 coin cells were fabricated in an Ar-filled glove box (MIKROUNA Super) using 0.3 M LiTFSI in PY13TFSI (v:v = 1:1), Celgard 2500 as the separator and lithium as the counter electrode.

[0259] Instruments and Characterization

[0260] High-resolution mass spectrometry (HRMS, m / z) was obtained by electrospray ionization (ESI) coupled to a quadrupole time-of-flight detector (Bruker maXis). UV–vis spectra were recorded on a Hitachi UH4150 UV–VIS–NIR spectrophotometer. Fourier transform infrared (FT-IR) spectra were obtained on a PerkinElmer FT-IR spectrometer. NMR spectra were recorded on Bruker Avance-300 and Avance-400 (400 MHz for 1 H, 100 MHz for 13 C) spectrometers. Chemical shifts (δ) were reported in parts per million (ppm) relative to TMS (used as an internal standard). The following abbreviations were used to describe the peak splitting patterns where appropriate: br = broad peak, s = singlet, d = doublet, t = triplet, q = quartet, m = multiplet, dd = doublet of doublets, dt = doublet of triplets. Coupling constants (J) were reported in Hertz (Hz). Thermal analyses were performed using a PerkinElmer TGA 8000 thermogravimetric analyzer. Crystallographic analysis XRD data were collected on an X-ray diffractometer (Rigaku SmartLab 9kW-Advance). EPR spectra were obtained on a commercial X-band CW EPR spectrometer (Bruker EMX) with the following settings: frequency, 9.4489 GHz; microwave power, 29.0 mW; modulation amplitude, 100 μT; time constant, 0.092 s.

[0261] Electrochemical measurements, including CV and EIS, were performed on a CHI Instruments electrochemical workstation (CHI660E). A Land CT2Battery tester was used to test the constant current charge–discharge and rate performance at different current densities in the potential range of 1.3–4.3 V.

[0262] The kinetics of the charge / discharge process can be determined by using the slope (b) in the plot of peak current against scan rate calculated with the following equation:

[0263] log i = b log v + log a

[0264] where i is the peak current, v is the scan rate, and a and b are constants. The value of b is the slope of the plot of log v and log i. When b = 0.5, the lithium-ion storage process is mainly controlled by diffusion. When b = 1, pseudocapacitive behavior dominates the lithium-ion storage process.

[0265] Example 1A

[0266] Preparation of Polynitroso Compound I

[0267] The synthetic scheme of polynitroso compound I (i.e., the polynitroso compound of formula (I) of the present invention) is shown in Figure 4 . Specifically, under an argon atmosphere, BF4NO (394 mg, 3.4 mmol) was added in one portion to a solution of commercially available 1,4-bis(trimethylsilyl)benzene 1 (222 mg, 1.0 mmol) in anhydrous CH3CN (15 ml) at room temperature. The reaction mixture was stirred for 30 minutes. Thereafter, the reaction was quenched by slowly dropping deoxygenated deionized water (30 mL). The precipitate formed after quenching was filtered, washed several times with deoxygenated deionized water, and then dried in the dark under vacuum conditions. The resulting product was stored in a nitrogen atmosphere. Yield: 120 mg (88%), yellow solid.

[0268] Example 1B

[0269] Preparation of Polynitroso Compound II

[0270] The synthetic scheme of polynitroso compound II (i.e., the polynitroso compound of formula (II) of the present invention) is shown in Figure 5 . Specifically, under an argon atmosphere, BF4NO (394 mg, 3.4 mmol) was added in one portion to a solution of commercially available 2 (298 mg, 1.0 mmol) in anhydrous CH3CN (15 ml) at room temperature. Thereafter, the reaction mixture was stirred for 30 minutes. The reaction was quenched by slowly dropping deoxygenated deionized water (30 mL). The precipitate formed after quenching was filtered, washed several times with deoxygenated deionized water, and then dried in the dark under vacuum conditions. The resulting product was stored in a nitrogen atmosphere. Yield: 200 mg (94%), light yellow solid.

[0271] Example 1C

[0272] Preparation of Polynitroso Compound III

[0273] The synthetic scheme of polynitroso compound III (i.e., the polynitroso compound of formula (III) of the present invention) is shown in Figure 6 Specifically, under an argon atmosphere, BF4NO (394 mg, 3.4 mmol) was added in one portion to a solution of commercially available 3 (374 mg, 1.0 mmol) in anhydrous CH3CN (15 ml) at room temperature. The reaction mixture was stirred for 30 minutes, after which the reaction was quenched by slowly adding deoxygenated deionized water (30 mL). The precipitate formed after quenching was filtered, washed several times with deoxygenated deionized water, and then dried in the dark under vacuum. The resulting product was stored in an atmosphere of N2 gas. Yield: 267 mg (95%), light yellow solid.

[0274] Example 1D

[0275] Preparation of polynitroso compound V

[0276] The synthetic scheme of polynitroso compound V (i.e., the polynitroso compound of formula (V) of the present invention) is shown in Figure 7 Specifically, the preparation involves two steps.

[0277] Step 1: 2,7-Bis(4-bromophenyl)pyrene 4 (5 g, 1 mmol) and anhydrous THF (250 mL) were added to a 500 mL three-necked round-bottom flask equipped with a magnetic stir bar. After cooling the solution to -78 °C, a solution of n-butyllithium (2.5 M in hexanes, 12 mL, 3 mmol) was added dropwise over 10 minutes, and the reaction mixture was stirred for an additional 30 minutes. Then, trimethylchlorosilane (7 mL, 6 mmol) was added dropwise to the above reaction mixture over 5 minutes, and the mixture was (slowly) warmed to room temperature and stirred for 3 hours. The resulting mixture was quenched with water (250 mL) and extracted with ethyl acetate (250 mL × 2). The organic phase was separated, washed twice with saturated brine, dried over anhydrous MgSO4. The organic phase was concentrated under reduced pressure, and the residue was washed several times with ethanol and dried in vacuo at 50 °C to give 5 as a white powder (Yield: 4 g, 80%). 1 1H NMR (400 MHz, CDCl3) δ 8.41 (s, 4H), 8.15 (s, 4H), 7.90 (s, 4H), 7.73 (s, 4H), 0.37 (s, 18H). 13 13C NMR (101 MHz, CDCl3) δ 134.24, 128.13, 127.55, 124.05, -0.84.

[0278] Step 2: Under an argon atmosphere, BF4NO (394 mg, 3.4 mmol) was added in one portion to a solution of 5 (498 mg, 1.0 mmol) in anhydrous CH3CN (15 ml) at room temperature. The reaction mixture was stirred for 30 minutes. Thereafter, deoxygenated deionized water (30 mL) was slowly added dropwise to quench the reaction. The precipitate formed after quenching was filtered, washed several times with deoxygenated deionized water, and then dried in the dark under vacuum. The resulting product was stored in a nitrogen atmosphere. Yield: 367 mg (89%), light yellow solid.

[0279] Example 1E

[0280] Preparation of Polynitroso Compound VI

[0281] The synthetic scheme of polynitroso compound V (i.e., the polynitroso compound of formula (VI) of the present invention) is shown in Figure 8 Specifically, the preparation includes two steps.

[0282] Step 1: 2,6-Bis(4-bromophenyl)naphthalene 6 (4.35 g, 1 mmol) and anhydrous THF (250 mL) were added to a 500 mL three-necked round-bottom flask equipped with a magnetic stir bar. After cooling the solution to -78 °C, a solution of n-butyllithium (2.5 M in hexanes, 12 mL, 3 mmol) was added dropwise over 10 minutes, and the reaction mixture was stirred for an additional 30 minutes. Then, trimethylchlorosilane (7 mL, 6 mmol) was added dropwise to the above reaction mixture over 5 minutes, and the temperature was (slowly) raised to room temperature and stirring was continued for 3 hours. The resulting mixture was quenched with water (250 mL) and extracted with ethyl acetate (250 mL × 2). The organic phase was separated, washed twice with saturated brine, and dried over anhydrous MgSO4. The organic phase was concentrated under reduced pressure, and the residue was washed several times with ethanol and dried in vacuo at 50 °C to give 7 as a white powder (Yield: 3.92 g, 92%). 1 HNMR (400 MHz, CDCl3) δ 8.08 (s, 1H), 7.98 (d, J = 8.4 Hz, 1H), 7.77 (m, 3H), 7.67 (d, J = 8.0 Hz, 2H), 0.34 (s, 9H). 13 C NMR (101 MHz, CDCl3) δ 141.39, 139.46, 138.57, 133.94, 132.92, 128.76, 126.70, 125.98, 125.56, -1.04.

[0283] Step 2: Under an argon atmosphere, BF4NO (394 mg, 3.4 mmol) was added in one portion to a solution of 7 (424 mg, 1.0 mmol) in anhydrous CH3CN (15 ml) at room temperature. The reaction mixture was stirred for 30 minutes. Subsequently, deoxygenated deionized water (30 mL) was slowly added dropwise to quench the reaction. The precipitate formed after quenching was filtered, washed several times with deoxygenated deionized water, and then dried under vacuum in the dark. The resulting product was stored under an N2 atmosphere. Yield: 276 mg (82%), light yellow solid.

[0284] Example 1F

[0285] Preparation of Polynitroso Compound VII, TPA-3NO

[0286] The synthetic scheme of polynitroso compound VII, TPA-3NO (i.e., the polynitroso compound of formula (VII) of the present invention) is shown in Figure 9 . Specifically, the preparation includes three steps.

[0287] Step (a): Triphenylamine (TPA) (25 g, 10.5 mmol) and silica gel (100 g) were added to a solution of NBS (56 g, 31.5 mmol, 3 equivalents) in DCM (1000 mL). The resulting suspension was stirred overnight at room temperature. The silica gel was removed by filtration, and the organic phase was washed thoroughly with water and saturated brine, and then dried over MgSO4. The solvent was removed under reduced pressure to obtain tris(4-bromophenyl)amine (TPA-3Br, 8) as a white solid (Yield: 45 g, 89%). 1 1H-NMR (400 MHz, CDCl3) δ 7.36 (d, J = 8.8 Hz, 6H), 6.92 (d, J = 8.8 Hz, 6H). 13 13C-NMR (101 MHz, CDCl3,): δ = 146.2, 132.7, 125.8, 116.2.

[0288] Step (b): 8 (14.46 g, 3 mmol) and anhydrous THF (600 mL) were added to a 1000 mL three-necked round-bottom flask equipped with a magnetic stir bar. After cooling the solution to -78 °C, a solution of n-butyllithium (2.5 M in hexane, 54 mL, 13.5 mmol) was added dropwise over 20 minutes, and the reaction mixture was stirred for an additional 30 minutes. Then, trimethylchlorosilane (22 mL, 18 mmol) was added dropwise to the above reaction mixture over 5 minutes, and the temperature was (slowly) raised to room temperature and stirring was continued for 3 hours. The resulting mixture was quenched with water (1000 mL) and extracted with ethyl acetate (500 mL × 2). The organic phase was separated, washed twice with saturated brine, and dried over anhydrous MgSO4. The organic phase was concentrated under reduced pressure, and the residue was washed several times with ethanol and dried in vacuo at 50 °C to give 4-(trimethylsilyl)-N,N-bis[4-(trimethylsilyl)phenyl]aniline (TPA-3TMS, 9) as a white powder (12.6 g, 91% yield). 1 H NMR (400 MHz, CDCl3) δ 7.41 (d, J = 8.2 Hz, 2H), 7.11 (d, J = 8.2 Hz, 2H), 0.29 (s, 9H). 13 C NMR (101 MHz, CDCl3) δ 148.13, 134.45, 134.11, 123.58, -0.77.

[0289] Step (c): Under an argon atmosphere, BF4NO (682 mg, 5.85 mmol) was added in one portion to a solution of 9 (600 mg, 1.3 mmol) in anhydrous CH3CN (42 ml, 0.03 M) at room temperature. The reaction mixture was then stirred for 30 minutes. Deoxygenated deionized water (42 mL) was added dropwise slowly to quench the reaction. The precipitate formed after quenching was filtered, washed several times with deoxygenated deionized water, and then dried in the dark under vacuum. The resulting sample (i.e., tris(4-nitrophenyl)amine, TPA-3NO) was stored under an N2 atmosphere. It is believed that the above synthetic procedure minimizes exposure to the environment and oxidation. Yield: 400 mg (92.6%), brown solid. 1 H NMR (400 MHz, CDCl3) δ 7.92 (d, J = 8.7 Hz, 6H), 7.36 (d, J = 9.0 Hz, 6H). 13 C NMR (101 MHz, CDCl3) δ 163.04, 151.37, 124.91, 123.54. HRMS C 18 H 12 N4O3 (M+H), calculated mass: 333.09822, found 333.09780.

[0290] Example 1G

[0291] Preparation of Polynitroso Compound VIII

[0292] The synthetic scheme of polynitroso compound VIII (i.e., the polynitroso compound of formula (VIII) of the present invention) is shown in Figure 10 as follows. Specifically, the preparation includes two steps.

[0293] Step (a): Add 1,3,5-tris(4-bromophenyl)benzene 10 (16 g, 3 mmol) and anhydrous THF (600 mL) to a 1000 mL three-necked round-bottom flask equipped with a magnetic stir bar. After cooling the solution to -78 °C, start dropwise addition of a solution of n-butyllithium (2.5 M in hexane, 54 mL, 13.5 mmol) and complete the addition within 20 minutes. Then, stir the reaction mixture for 30 minutes. Next, dropwise add trimethylchlorosilane (22 mL, 18 mmol) to the above reaction mixture and complete the addition within 5 minutes. (Slowly) warm to room temperature and continue stirring for 3 hours. Quench the resulting mixture with water (1000 mL) and extract with ethyl acetate (500 mL × 2). Separate the organic phase, wash it twice with saturated brine, and dry it over anhydrous MgSO4. Concentrate the organic phase under reduced pressure, wash the residue several times with ethanol, and dry it in vacuo at 50 °C to obtain 11 as a white powder (yield: 14 g, 90%). 1 1H NMR (300 MHz, CDCl3) δ 7.79 (s, 3H), 7.71–7.62 (m, 12H), 0.33 (s, 27H). 13 13C NMR (101 MHz, CDCl3) δ 142.49, 141.70, 139.80, 134.11, 126.87, 125.46, 77.52, 77.20, 76.88, -0.86.

[0294] Step (b): Under an argon atmosphere, add BF4NO (227 mg, 1.95 mmol) in one portion to a solution of 11 (200 mg, 0.38 mmol) in anhydrous CH3CN (12 ml) at room temperature. Stir the reaction mixture for 12 minutes. Then, slowly add deoxygenated deionized water (30 mL) to quench the reaction. Filter the precipitate formed after quenching, wash it several times with deoxygenated deionized water, and then dry it in the dark under vacuum conditions. Store the resulting product in an N2 atmosphere. Yield: 140 mg (93%), green solid. 1 1H NMR (300 MHz, DMSO-d6) δ 8.39 (d, J = 8.5 Hz, 2H), 8.37 (s, 1H), 8.11 (d, J = 8.3 Hz, 2H).

[0295] Example 1H

[0296] Preparation of polynitroso compound X

[0297] The synthetic scheme of polynitroso compound X (i.e., the polynitroso compound of formula (X) of the present invention) is shown in Figure 11 as follows. Specifically, the preparation includes two steps.

[0298] Step (a): Dissolve commercially available 1,3,5-tris(4-bromophenyl)benzene 12 (5.0 g, 11.42 mmol) in 250 mL of a solvent (THF / toluene, (v / v): 1:1). Then add 1-bromo-4-(trimethylsilyl)benzene (9.4 g, 41 mmol), PdCl2(PPh3)2 (961 mg, 12 mol%), and a solution of K2CO3 (9.7 g, 61.5 mmol) in 20 mL of distilled water thereto. The reaction mixture is refluxed at 110 °C for 40 hours, then quenched with water and extracted three times with dichloromethane. Then the combined organic layers are dried over MgSO4. After evaporation of the solvent, the crude product is purified by flash chromatography using hexane as the eluent to obtain 6.9 g of pure compound 13 as a colorless solid (unstable under UV (254 / 365 nm) light), with a yield of 81%. 1 H NMR (400 MHz, CDCl3) δ 7.90 (s, 3H), 7.81 (d, J = 8.4 Hz, 6H), 7.76 (d, J = 8.4 Hz, 6H), 7.69 (d, J = 1.8 Hz, 12H), 0.37 (s, 27H). 13 C NMR (101 MHz, CDCl3) δ 142.09, 141.14, 140.51, 140.20, 139.63, 134.09, 127.90, 127.77, 126.57, 125.15, -0.87.

[0299] Step (b): Under an argon atmosphere, add BF4NO (158 mg, 1.36 mmol) to a solution of 13 (200 mg, 0.26 mmol) in anhydrous CH3CN (10 ml) at room temperature all at once. The reaction mixture is stirred for 30 minutes. Thereafter, the reaction is quenched by slowly dropping deoxygenated deionized water (10 mL). The precipitate formed after quenching is filtered, washed several times with deoxygenated deionized water, and then dried in the dark under vacuum. The obtained product is stored in an N2 atmosphere. Yield: 160 mg (96%), green solid.

[0300] Example 1I

[0301] Preparation of polynitroso compound XI

[0302] The synthetic scheme of polynitroso compound XI (i.e., the polynitroso compound of formula (XI) of the present invention) is shown in Figure 12 . Specifically, the preparation includes two steps.

[0303] Step (a): Add 1,1,2,2-tetrakis(4-bromophenyl)ethylene 14 (19.3 g, 3 mmol) and anhydrous THF (1000 mL) to a 2000 mL three-necked round-bottom flask equipped with a magnetic stir bar. Cool the solution to -78 °C. Dropwise add a solution of n-butyllithium (2.5 M in hexane, 72 mL, 18 mmol) over 20 minutes. Continue to stir the reaction mixture for 30 minutes. Then, dropwise add trimethylchlorosilane (29 mL, 24 mmol) to the above reaction mixture, slowly warm to room temperature and continue stirring for 3 hours. Quench the resulting mixture with water (1000 mL) and extract with ethyl acetate (500 mL × 2). Separate the organic phase, wash it twice with saturated brine, and dry it over anhydrous MgSO4. Concentrate the organic phase under reduced pressure, wash the residue several times with ethanol, and dry it in vacuo at 50 °C to obtain 15 (16 g, 86% yield) as a white powder. 1 1H NMR (400 MHz, CDCl3) δ 7.24 (d, J = 7.9 Hz, 2H), 7.00 (d, J = 7.9 Hz, 2H), 0.22 (s, 9H). 13 13C NMR (101 MHz, CDCl3) δ 144.24, 141.38, 138.32, 132.65, 130.73, -0.93.

[0304] Step (b): Under an argon atmosphere, add BF4NO (252 mg, 2.1 mmol) all at once to a solution of 15 (200 mg, 0.32 mmol) in anhydrous CH3CN (10.7 ml) at room temperature. Stir the reaction mixture for 30 minutes. Then, quench the reaction with deionized water (12 mL). Filter the precipitate formed after quenching, wash it several times with deionized water, and then dry it in the dark under vacuum. Store the resulting product in an N2 atmosphere. Yield: 120 mg (83%), yellow-green solid. 1 1H NMR (300 MHz, DMSO-d6) δ 7.82 (d, J = 8.5 Hz, 1H), 7.47 (d, J = 8.5 Hz, 1H). 13 13C NMR (101 MHz, DMSO-d6) δ 163.97, 148.87, 142.09, 132.45, 120.83.

[0305] Example 2

[0306] Characterization of Polynitro Compound VII, TPA-3NO

[0307] The synthesis of TPA-3NO (i.e., the polynitro compound of formula (VII)) begins with the preparation of the intermediate TPA-3Br by brominating TPA for 12 h at room temperature ( Figure 9 ). TPA-3Br was treated with n-BuLi at -78 °C and then trimethylchlorosilane was added to form the key intermediate TPA-3TMS in 91% yield. Then, the TPA-3TMS intermediate was nitrosated with BF4NO to readily prepare the target product TPA-3NO in quantitative yield. The obtained light brown solid was shown to be of high purity after a simple work-up procedure as detailed in Example 1F by nuclear magnetic resonance (NMR) spectroscopy ( Figures 13A to 15B ). For subsequent comparative studies, (comparative compound) 1-bromo-4-nitrobenzene was prepared in the same manner ( Figure 16 ). The NMR spectrum of the prepared 1-bromo-4-nitrobenzene is shown in Figures 17A to 17B . 1 1H NMR (400 MHz, CDCl3) δ 7.79 (s, 4H); 13 13C NMR (101 MHz, CDCl3) δ 163.97, 132.85, 131.97, 122.33.

[0308] As confirmed by Figure 18A and 18B the 9 F and 11 B NMR spectra, no inorganic residual impurities were observed in the resulting TPA-3NO even after long spectral scans. Additionally, as shown in Figure 19 , the nitroso groups on TPA-3NO showed considerable stability and could be stored in solution for several weeks without significant degradation. Thermogravimetric analysis (TGA) also indicated that TPA-3NO had considerable thermal stability with a weight loss of less than 5% upon continuous heating at 200 °C for 180 min ( Figure 20 ).

[0309] The form in which TPA-3NO exists (i.e., monomer / dimer / oligomer / polymer) was determined by ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, and single crystal X-ray diffraction (SCXRD). The UV-Vis absorption spectra of TPA-3NO were recorded in a dilute chloroform solution (10 -5 M, Figure 21A ) as well as in a thin film ( Figure 21B ). The maximum absorbance near 440 nm in chloroform is the π*←n of the nitroso monomer ( NAbsorption characteristics. The absorption bands at 256 and 274 nm correspond to the π*←n O and π*←π transitions of the nitroso group. The optical band gap calculated based on the onset absorption in the thin film is E g opt = 2.27 eV.

[0310] The monomeric structural characteristics of TPA-3NO were further confirmed by FT-IR analysis. As Figure 21C shown, the characteristic absorption peak at 1486 cm -1 belongs to the vibrational absorption of the nitroso group in the monomer. The strongest signal at 1101 cm -1 in the FT-IR spectrum can be attributed to the C-N=O stretching vibration of the monomer, and this absorption signal usually appears in the FT-IR absorption spectra of polynitroso compounds. At the same time, the strong absorption band at 1266 cm -1 (due to the vibration of the central N-C(sp 2 ) stretching), the strong absorption band at 1581 cm -1 and the shoulder peak near 1486 cm -1 all belong to the vibrational absorption of the benzene ring in TPA-3NO.

[0311] Single crystals of TPA-3NO suitable for SCXRD analysis can be easily obtained by (slowly) evaporating a saturated chloroform solution of TPA-3NO. As Figure 21D shown, the single crystal structure shows that N1 is in the C1C1C7 plane, while the three p-phenylene rings A, B, and C are inclined at about 32.1°, about 32.1°, and about 46.1° respectively from the said plane. The C=C double bond (C=C double bond) on the benzene ring is about The bond (C-N bond) connecting the nitroso group and the benzene ring is about The N=O bond length in the nitroso group is about which is significantly smaller than the N=O bond length in general nitroso compounds (about ), indicating that the nitroso group in TPA-3NO may have unique properties.

[0312] As is well known, the nitroso group is a strong electron-withdrawing substituent, while the triphenylamine (TPA) group is an electron-donating substituent. Therefore, TPA-3NO is a donor-acceptor (DA) molecule with a strong electron push-pull effect (i.e., the radical is stabilized by the synergistic action of the electron-withdrawing substituent and the electron-donating substituent). To study the electronic behavior in TPA-3NO, electron paramagnetic resonance (EPR) test analysis was carried out. As Figure 21EAs shown, TPA-3NO shows a strong signal in the EPR spectrum with a g value of approximately 2.0051, indicating that TPA-3NO has a molecular structure with free radicals. Generally speaking, a single nitroso molecular structure does not have / does not contain free radicals. At the same time, the comparative molecule 1-bromo-4-nitrobenzene prepared in the same way shows a negligible EPR signal (i.e., 1-bromo-4-nitrobenzene does not have free radical absorption in the EPR test)( Figure 21E ). And no Figure 18A and 18B observed in 19 F and 11 B-NMR spectra 19 F or 11 B signal, indicating that there are no counterions in the prepared solid. Therefore, the free radical signal in 21E originates from the inherent properties of neutral, high-purity TPA-3NO.

[0313] The property of TPA-3NO having free radicals is further supported by fluorescence test experiments. As Figure 22 can be seen, TPA-3NO itself has no fluorescence, while its similar structure molecule tris(4-nitrophenyl)amine has obvious fluorescence. Since the excitons in the molecule are quenched by unpaired electrons, TPA-3NO does not have fluorescence properties. Unexpectedly, the inventors found that the free radical property of TPA-3NO shows significant persistence in the atmospheric environment, and even after 6 months, the free radical property still does not fade ( Figure 21F ). Given the excellent structural stability and persistent free radical characteristics of TPA-3NO, TPA-3NO shows potential application value in fields such as rechargeable batteries (e.g., lithium-ion batteries (LIB), organic radical batteries (ORB), etc.).

[0314] Example 3

[0315] Electrochemical performance of polynitroso compound VII, TPA-3NO

[0316] To study the electrochemical performance of TPA-3NO and its potential application as an energy storage material, TPA-3NO was assembled as the cathode of a LIB with an electrolyte of 0.3M LiTFSI-PY13TFSI (PY13TFSI = N-methyl-N-propylpyrrolidinium bis(trifluoromethanesulfonyl)amide). Cyclic voltammetry (CV) curves were recorded for the experimental results in the voltage range of approximately 1.3 - 4.3V (vs. Li / Li -1 ) at a scan rate of 0.2mV s + ( Figure 23)。The results show that there are two oxidation peaks at about 2.6 V / 3.8 V and two reduction peaks at about 2.4 V / 3.7 V. Meanwhile, the CV curve shows that although the peak area changes slightly, the peak shape remains basically intact, indicating that the lithium-ion insertion and extraction process is a completely reversible process.

[0317] The rate performance of the TPA-3NO cathode was tested at various current densities ( Figure 24A ). After cycling at different current densities, the discharge capacity of TPA-3NO can be stabilized at nearly 270 mAh g -1 , where the current density returns to 50 mA g -1 , and the discharge capacity can recover to 96% of the initial capacity, demonstrating the good reversibility of the electrode material. As the current density increases, the cathode still exhibits excellent capacity. For example, capacities of 181 and 117 mAh g -1 were achieved at 500 and 1000 mA g -1 respectively, indicating its excellent performance as a radical cathode material in LIBs. In addition, after 100 cycles at a current density of 100 mA g -1 , the specific capacity remains 300 mAh g -1 ( Figure 24B ), which is much higher than the results of previously reported radical materials ( Figure 24C ). In addition, it can be intuitively seen from the charge-discharge curves ( Figure 25A and 25B ) that even when the current density is increased to 1000 mA g -1 , high capacitance and stability can still be maintained in a wide voltage window of 1.3 - 4.3 V.

[0318] To further understand the rate performance of the TPA-3NO electrode, a series of CV curves were recorded at different scan rates of 0.2, 0.4, 0.6, 0.8, and 1 mV s -1 . It can be seen from Figure 26A that as the scan rate increases, although the heights of the oxidation-reduction peaks are different. However, their shapes are highly consistent, indicating that the electrochemical polarization of the electrode can be ignored. To explain the reason why the performance of the TPA-3NO electrode is so excellent, the kinetic process was explored. As Figure 26B shows, a small slope value (i.e., b less than 1) clearly proves that the charge storage is a quasi-capacitive process controlled by fast surface. In addition, the diffusion control and capacitive contribution in the battery system can also be quantitatively analyzed separately ( Figure 26C ). The capacitive contribution was determined to be 46% at a scan rate of 0.2 mV s -1 , and it is 46% at 1.0 mV s -1At a scanning rate of, it is further increased to 66%. The results are consistent with the above analysis. Undoubtedly, the kinetically fast pseudocapacitive process endows the obtained battery system with excellent rate performance.

[0319] In addition, the long-term cycling performance of the TPA-3NO cathode was also investigated. Notably, at 1 A g -1 , after 1000 cycles, a capacity of approximately 140 mAh g -1 (85%) was retained ( Figure 26D ), which exceeds most of the reported organic radical electrode materials ( Figure 24C ). Notably, even at 2 A g -1 , after 2000 cycles, a capacity of approximately 114 mAh g -1 was achieved ( Figure 26E ). It is believed that having such a wide voltage window (about 1.3 - 4.1 V) and such long cycling stability (> about 2000 cycles) is the discovery of very unexpected characteristics in the ORB.

[0320] In addition, electrochemical impedance spectroscopy (EIS) was performed at 10 -2 Hz to 10 5 Hz ( Figure 27 ). Although the impedance increases with cycling, it eventually stabilizes. This trend is consistent with the cycling performance described above, where the capacity initially decreases and finally stabilizes.

[0321] The charge and discharge mechanisms of TPA-3NO were investigated. As Figure 28 shown, the entire redox process can be divided into four stages. First, the charge-discharge process involves the insertion and extraction of Li + with the nitroso groups in TPA-3NO, and this process belongs to the n-type charge-discharge process. At the same time, like other TPA-based redox-active organic electrode materials, during the charge-discharge process, there is the binding and separation between the central nitrogen atom on TPA and the TFSI - anions in the electrolyte, and this process belongs to the p-type charge-discharge process. Specifically, during discharge, TPA-3NO is first reduced by accepting three electrons to form a fully reduced state. By inserting three Li + , the three N=O redox-active groups are converted to ═N-O-Li. Subsequently, TPA-3NO is oxidized by losing three electrons and returns to its initial state during charging, which is accompanied by the extraction of three Li +Delithiation. Briefly, the first two stages are related to the redox process of the n-type doping reaction of the N=O group. Subsequently, the last two processes are attributed to the p-type doping of the C-N moiety. When used as the cathode material of a lithium-ion battery, the redox-active groups of the central C-N and peripheral N=O jointly provide a theoretical capacity of up to 323 mAh g -1 .

[0322] The proposed redox mechanism was further verified separately by ex-situ FT-IR and X-ray photoelectron spectroscopy (XPS). During the discharge process, as Li + is embedded in the N=O group to form =N-O-Li, the peak of the nitroso group at 1486 cm -1 in the FT-IR spectrum gradually weakens ( Figure 29A and 29B ). At the same time, the peak corresponding to the =N-O-Li bond at 1040 cm -1 appears and gradually strengthens. However, during the charging process, Li + leaves the N-O-Li unit, and the N-O-Li bond gradually disappears, accompanied by the reappearance of the N=O bond. In addition, during the interaction between the N=O group and Li + , similar changes are also observed near the stretching of the benzene ring bond (1581 cm -1 ). In addition, it is worth noting that the peak change at 1410 cm -1 belongs to the cis-azodioxo bond because the reversible dimerization of the nitroso group also occurs concomitantly, which is a common phenomenon in nitroso derivatives. It is believed that these results have demonstrated that N=O is the reversible redox-active center during the charging and discharging processes.

[0323] In addition, it is believed that the ex-situ XPS results consolidate the proposed mechanism and the obtained results. As Figures 30A to 30E shown, when the battery is discharged from the original state to 1.3 V, a new C peak appears at 286.7 eV, thus revealing the state change of the benzene ring. After charging to 4.3 V, the peak weakens and gradually returns to its initial state. At the same time, N 1s ( Figure 30B ), a new n peak appears at about 398.6 eV, suggesting the interaction between the TFSI - anion and the central N atom, thus forming the TFSI---TPA-3NO structure. However, when the discharge reaches 1.3 V, this peak also disappears. The peak changes of F 1s ( Figure 30D , about 285.2 eV) and S 2p ( Figure 30E , about 169.8 eV) further prove the direct insertion and extraction of the TFSI - anion. Therefore, N 1s, F 1s, and S 2p all prove the TFSI -The intercalation and dissociation of anions during charge and discharge processes are presented, and the characteristics of TPA-3NO as a p-type material are revealed.

[0324] On the other hand, a new N peak appears at approximately 402.7 eV when discharging to 1.3 V ( Figure 30B ), which can be attributed to the formation of C=N-O during the lithiation process - . After charging to 4.3 V, the peak gradually disappears. In addition, similar changes are observed in the O 1s spectrum ( Figure 30C ). It can be seen that as discharging to approximately 1.3 V, a new O peak appears at approximately 532.2 eV and then disappears, which can be attributed to the formation of the N-O-Li bond, thus demonstrating the successful reversible intercalation and deintercalation of Li + towards the N=O bond. Therefore, the n-type characteristics of TPA-3NO are also verified by the N 1s and O 1s spectral changes. Based on these results, it is believed that the proposed charge / discharge mechanism of TPA-3NO in LIB has been affirmed.

[0325] It should be understood that the above only illustrates and describes embodiments that can implement the present invention, and modifications and / or changes can be made thereto without departing from the spirit of the present invention.

[0326] It should also be understood that certain features of the present invention described in the context of separate embodiments for clarity can also be provided in combination with a single embodiment. Conversely, various features of the present invention described in the context of a single embodiment for brevity can also be provided separately or in any suitable sub-combination.

[0327] All references specifically cited herein are incorporated herein by reference in their entirety. However, the citation or incorporation of such references does not necessarily admit their suitability, citable nature, and / or availability as prior art against / for the present invention.

Claims

1. A polynitroso compound, wherein the compound comprises a structure having the following formula: Formula (VII).

2. An energy storage device having a cathode comprising the polynitroso compound according to claim 1.

3. The energy storage device according to claim 2, wherein the device is a rechargeable lithium-ion battery.

4. The energy storage device according to claim 2, wherein the device has a stable discharge capacity of 270 mA h g -1 to 1 A g -1 at a current density of -1 to 117 mA h g -1 within a voltage window of 1.3 V to 4.3 V.

5. The energy storage device according to claim 2, wherein the device has a specific capacity of 300 mA h g -1 after 100 charge / discharge cycles at a current density of 100 mA g -1 .

6. The energy storage device according to claim 2, wherein the device has a capacity retention rate of 85% after 1000 charge / discharge cycles at a current density of 1 A g -1 .

7. A method for preparing the polynitroso compound according to claim 1, the method comprising the following steps: a) providing a precursor compound comprising two or more terminal trifluoroborate groups or silyl groups; and b) nitrosating the precursor compound with a nitrosating agent, wherein the precursor compound is selected from the group consisting of: Formula (B1) Formula (B2) wherein, L2 is a nitrogen atom.

8. The method according to claim 7, wherein the nitrosating agent comprises a nitronium salt.

9. The method according to claim 8, wherein the nitronium salt is selected from the group consisting of: nitrosyl bromide, nitrosyl chloride, nitrosyl sulfuric acid, potassium nitrite, sodium nitrite, silver nitrite, nitronium tetrafluoroborate, and combinations thereof.

10. The method according to claim 7, wherein the nitrosation is carried out under neutral or acidic conditions.

11. The method according to claim 10, wherein the acidic conditions are adjusted by hydrochloric acid, hydrobromic acid, sulfuric acid, or combinations thereof.

12. The method according to claim 7, wherein the precursor compound is provided in the form of a reaction solvent mixture.

13. The method according to claim 12, wherein the reaction solvent is selected from the group consisting of: 1,2-dichlorobenzene, dichloromethane, 1,2-dichloroethane, tetrahydrofuran, n-hexane, heptane, ethyl acetate, toluene, acetonitrile, and combinations thereof.

14. The method according to claim 13, wherein the reaction solvent is acetonitrile.

15. The method according to claim 7, wherein step b) comprises the step of preparing a reaction mixture of the precursor compound and the nitrosating agent in an A:B molar ratio, wherein A is from 2 to 4 and B is from 3 to 10.

16. The method according to claim 9, wherein the nitronium salt is nitronium tetrafluoroborate.